Laminin-binding epitope on gp43 from Paracoccidioides brasiliensis is recognized by a monoclonal antibody raised against Staphylococcus aureus laminin receptor - Vicentini, A. P.; Moraes, J. Z.; Gesztesi, J. L.; Franco, M. F. [UNESP]; De Souza, W.; Lopes, J. D. (Oxford University Press (OUP), 1997)
Adhesion is regarded as an important step in the pathogenesis of several microorganisms. Thus, the ability to recognize extracellular matrix proteins, such as laminin or fibronectin, has been correlated with invasiveness. Studying the already characterized laminin-binding protein of Paracoccidioides brasiliensis, the 43 kDa glycoprotein (gp43), we evaluated whether MAb 1.H12, raised against the laminin-binding protein from Staphylococcus aureus, cross-reacts with that fungal protein. By immunoblot analysis we show that MAb 1.H12 recognizes gp43. This interaction is able to inhibit the laminin-mediated adhesion to epithelial cells as well as the P. brasiliensis infection in vivo. Moreover, through immunoenzymatic assays, we show that MAb 1.H12 recognizes gp43 in solid phase and that this interaction is partially inhibited by the addition of anti-gp43 MAbs. These results show that MAb 1.H12 recognizes the gp43, suggesting the presence of an epitope similar to those found in the other laminin-binding proteins from phylogenetically very distant cells. These findings reinforce the possibility of evolutionary conservation of such epitopes.
Keywords: anti-S. aureus; Laminin-binding; Mab 1.H12; P. brasiliensis; epitope; glycoprotein; laminin; laminin binding protein; laminin receptor; monoclonal antibody; adhesion; cell invasion; controlled study; evolution; extracellular matrix; nonhuman; paracoccidioides brasiliensis; phylogeny; staphylococcus aureus; Animals; Antibodies, Monoclonal; Binding Sites; Cell Adhesion; Cell Line; Cricetinae; Dogs; Epithelium; Epitopes; Extracellular Matrix Proteins; Granuloma; Humans; Kidney; Laminin; Lung Neoplasms; Male; Microscopy, Electron, Scanning; Paracoccidioides; Receptors, Laminin; Staphylococcus aureus; Testis; Paracoccidioides brasiliensis